Genome-wide analysis of DNA G-quadruplex motifs across 37 species provides insights into G4 evolution - Feng Wu (Nature Portfolio, 2021)
Wu, Niu, Cui et al characterize G4 motifs across 37 species by bioinformatics, revealing that G4 complexity increases with evolution and as well as an antagonistic relationship between the potential G4s and DNA methylation sites.